Bursyylis - singers of good: mystical practices and narratives - Oleg I. Ulyashev (Publishing house "Sreda", 2024)
The article is devoted to the mystical component of the religious practice of the upper Vychegdas Orthodox community of bursyylisy 'singers of good' (Komi Republic). The community was organized by Stepan Ermolin, a native of the Myeldinsky pogost, a translator of sacred texts from Church Slavonic and Russian into the Komi language, in the 1900s. Religious services of the "singers of good" were held in the Komi-Zyryan language, in continuation of the traditions established in the 14th century by the First Baptist of the Vychegdas Perm people (ancestors of the Komi-Zyrians) St. Stephen, the first bishop of Perm. The current of bursylisy spread along the upper Vychegda, communities arose in the villages of Myeldino, Usty-Nem, Pozheg, Skorodum, Vylygort, Bogorodsk. For some community members, spirit-vision or "communication with the saints / the Mother of God / Christ" in a state of trance was typical. The article attempts to reconstruct the conditions, ways and methods of achieving altered states of consciousness by spirit-seers, and also explains the reasons for the sharp decline of this phenomenon in the 1950s.